Pemahaman Aliran Moneter dan Fiskal Dalam Konsep Permintaan Uang di Indonesia: Sebuah Pendekatan Literatur - Hamzah, Muhammad Zilal; Sofilda, Eleonora; Eferedo, Eferedo (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2023)
Institutions such as the Ministry of Finance and the Central Bank have a strategic role in determining the macro direction of an economy. Not only that, other institutions, such as the Financial Services Authority (OJK) and the Deposit Insurance Corporation (LPS), also support the creation of conducive macroeconomic conditions, especially through the monetary sector. Monetary and fiscal policies are the main instruments used by the Indonesian government to intervene in the economy at a macro level. However, in theory, both still leave debate regarding their level of effectiveness. Therefore, this study aims to analyze the effectiveness of these two policies and is expected to have implications for Public Service Agencies, especially institutions in the financial ecosystem. This study uses a Meta-Analysis approach using OpenMee software to calculate the combined effect on each existing data. The main findings in this study show that only the income variable has a significant influence on the demand for money in the short term. However, the elasticity of the interest rate variable was found to be more inelastic. This condition is in accordance with monetarist assumptions which consider money as a form of substitute for real assets. Indonesia's lagging condition of financial literacy and inclusion can be a factor that explains that people have a substitution preference for real assets compared to financial assets. This study has the implication that monetary policy is more effective in encouraging output growth compared to fiscal policy. Therefore, it is hoped that the role of the financial authorities will be to support monetary policy further.